Monsters University - Scanlon, Dan; Rae, Kori; Lasseter, John; Docter, Pete; Stanton, Andrew; Unkrich, Lee; Gerson, Daniel, 1966-2016; Baird, Robert L.; Crystal, Billy; Goodman, John, 1952-; Buscemi, Steve, 1957-; Mirren, Helen; et al. (Burbank, California Buena Vista Home Entertainment, 2013)
Mike Wazowski and James P. Sullivan are an inseparable pair, but that wasn't always the case. From the moment these two mismatched monsters met they couldn't stand each other. Monsters University unlocks the door to how Mike and Sulley overcame their differences and became the best of friends.
DVD release of the 2013 motion picture.
Bonus features include The blue umbrella (MPAA rating: G ; 7 min.) / written & directed by Saschka Unseld ; executive producer, John Lasseter ; produced by Marc S. Greenberg -- Audio commentary (by director Dan Scanlon, producer Kori Rae, and story supervisor Kelsey Mann).
Original score composed and conducted by Randy Newman ; film editor, Greg Snyder ; production designer, Ricky Nierva ; supervising animator, Scott Clark ; directors of photography, Matt Aspbury (camera), Jean-Claude Kalache (lighting) ; art directors, Jason Deamer (character design), Daisuke "Dice" Tsutsumi (lighting design & character shading), Robert Kondo (set design & shading); executive producers, John Lasseter, Pete Docter, Andrew Stanton, Lee Unkrich ; story by Dan Scanlon, Daniel Gerson & Robert L. Baird.
Blue umbrella: editor, Jason Hudak ; supervising animator, Ross Haldane Stevenson ; music by Jon Brion ; production designer, Jay Shuster ; vocal performance by Sarah Jaffe.
Billy Crystal, John Goodman, Steve Buscemi, Helen Mirren, Peter Sohn, Joel Murray, Sean P. Hayes, Dave Foley, Charlie Day, Alfred Molina, Tyler Labine, Nathan Fillion, Aubrey Plaza, Bobby Moynihan, Noah Johnston, Julia Sweeney, Bonnie Hunt, John Krasinski, Bill Hader, Beth Behrs, Bob Peterson, John Ratzenberger.
MPAA rating: G CHV rating: G.
Keywords: Monsters -- Drama; Friendship -- Drama; College students -- Drama; Children's films; Animated films -- United States; Feature films -- United States; Juvenile works; Drama; Video recordings for people with visual disabilities; Video recordings for the hearing impaired